The awareness and interest of UiTM Pahang population towards the virtual tour / Anis Hasliza Abu Hashim, Maslina Abdul Aziz and Mazliana Hasnan - Abu Hashim, Anis Hasliza; Abdul Aziz, Maslina; Hasnan, Mazliana (2008)
The development of virtual reality is still expanding which leads to the growth of the increasingly popular virtual tour technology. The use of 360-degree panoramic images that allows people to view the environment without having to physically be at the location has increased with more online users experiencing this technology. This paper describes the awareness of UiTM Pahang population on the technology of virtual tour. It also includes factors that influence the interests of UiTM Pahang population to use this technology. Virtual tour can enhance the presence of UiTM Pahang as well as provide much information to remote and prospective users.